CAPITAL OUTFLOWS BY RUSSIAN MULTINATIONALS: EXPLANATION OF WIDER EUROPE’S DOMINANCE - A. V. Kuznetsov (Vestnik MGIMO-Universiteta)
Regulation of capital outflows has become an important task for the Russian economic policy. Such regulation needs the real picture of the Russian outward foreign direct investment (FDI) geography without distortions by official statistics with its data on indirect FDI via offshores. The article is based on new empirical FDI data collected by the author. This information shows the dominance of Wider Europe in the Russian outward FDI geography. The regional character of many Russian multinationals can be explained by several key factors, including the importance of market-seeking FDI motives, Russian oligarchs’ attempts at increasing their bargaining power and relatively comfortable business climate of neighboring countries in combination with the lack of experience and weak state support of Russian investors abroad. At the end of the article, some measures for regulation of FDI outflows are offered for diversification of the Russian outward FDI geography. Russian companies need information and institutional support which is a crucial type of incentives for initial stages of their investment projects abroad. Bilateral investment and double taxation treaties are main measures of institutional support. State insurance of investments is a key element of support for mature projects abroad.